1979
DOI: 10.1042/bj1840355
|View full text |Cite
|
Sign up to set email alerts
|

Insulin action on adipocytes. Evidence that the anti-lipolytic and lipogenic effects of insulin are mediated by the same receptor

Abstract: 1. The dose-response relationships of insulin stimulation of lipogenesis and inhibition of lipolysis were studied simultaneously by using rat adipocytes to determine whether these different effects of insulin are mediated through the same or different sets of receptors. 2. The sensitivity (defined as the concentration of insulin required to produce a half-maximal effect) of the stimulated lipogenic response to insulin was not significantly different from the sensitivity of the anti-lipolytic response to insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

1981
1981
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 22 publications
3
16
1
Order By: Relevance
“…Previous studies with rat fat cells suggested that the degree of antilipolysis induced by insulin depends on the rate of lipolysis before the addition of insulin [25]. Thus, the antilipolytic effect of insulin is more pronounced in rodent adipose tissue when lipolysis is raised.…”
Section: Resultsmentioning
confidence: 87%
“…Previous studies with rat fat cells suggested that the degree of antilipolysis induced by insulin depends on the rate of lipolysis before the addition of insulin [25]. Thus, the antilipolytic effect of insulin is more pronounced in rodent adipose tissue when lipolysis is raised.…”
Section: Resultsmentioning
confidence: 87%
“…This higher antilipolytic action of insulin in early gestation should play a very important role in the maintenance of fat deposition. Previous studies with rat fat cells have hypothesized that the degree of antilipolysis induced by insulin depends on the rate of lipolysis before the addition of the hormone (56). Thus the antilipolytic effect is more pronounced when the lipolysis is raised.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, because the ␤-adrenoceptor activity is impaired when nonpregnant animals become hyperinsulinemic by means of the euglycemic hyperinsulinemic clamp (23), we can speculate that the lower catecholamine-stimulated lipolysis in late gestation could be a consequence of decreased adrenoceptor activity secondary to maternal hyperinsulinemia. The antilipolytic effect of insulin is considered the most sensitive of its metabolic actions (56), so it requires a much lower insulin concentration (1 nM in our study) than other response sites like the stimulation of glucose transport (Ͼ10 nM for glucose uptake and lipogenesis). Hence, even in insulin resistance states, in which glucose transport is impaired, sensitivity to insulin's antilipolytic effect is relatively preserved.…”
Section: Discussionmentioning
confidence: 99%
“…This is most easily shown in isolated adipocytes from young rats and is illustrated in Fig. 1 (Thomas et al 1979). What the 1950s biochemists failed to take notice of was the considerable uptake of glucose that takes place in all tissues even when insulin is absent.…”
Section: Autacoids -Excitatory Substances Chalones -Inhibitory Substamentioning
confidence: 99%